5-Formyluracil as a cornerstone for aluminum detection in vitro and in vivo: a more natural and sustainable strategy. Issue 93 (6th November 2018) - Zou, Guangrong; Liu, Chaoxing; Cong, Chen; Fang, Zhentian; Yang, Wei; Luo, Xiaomeng; Jia, Shaokang; Wu, Fan; Zhou, Xiang
Abstract : 5-Formyluracil (5fU) based probes were designed and synthesized to detect Al 3+ ions in vitro and in biological systems. Abstract : 5-Formyluracil (5fU) based probes were designed and synthesized to detect Al 3+ ions in vitro and in biological systems. These probes were synthesised using furan-2-carbohydrazide (fr) and 5fU derivatives. We also selectively labelled 5-formyluracil in DNA with the help of Al 3+ .